2007
DOI: 10.1523/jneurosci.0212-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Spare Respiratory Capacity Rather Than Oxidative Stress Regulates Glutamate Excitotoxicity after Partial Respiratory Inhibition of Mitochondrial Complex I with Rotenone

Abstract: Partial inhibition of mitochondrial respiratory complex I by rotenone reproduces aspects of Parkinson's disease in rodents. The hypothesis that rotenone enhancement of neuronal cell death is attributable to oxidative stress was tested in an acute glutamate excitotoxicity model using primary cultures of rat cerebellar granule neurons. As little as 5 nM rotenone increased mitochondrial superoxide (O 2 ⅐Ϫ ) levels and potentiated glutamate-induced cytoplasmic Ca 2ϩ deregulation, the first irreversible stage of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
242
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(254 citation statements)
references
References 38 publications
10
242
1
1
Order By: Relevance
“…The apparent contradictory effects of minocycline on mitochondrial respiration (i.e., stimulation vs. inhibition) have been, in part, previously reported for others drugs such as local anaesthetics [50]. Since activation of NMDA receptors responsible for excitotoxicity imposes a high energetic demand on the in situ mitochondria [51] one could hypothesize that minocycline exerts its neuroprotective effect by affecting bioenergetic functions of mitochondria. Indeed, this effect could be responsible for the recent report showing that minocycline has a harmful effect on patients with ALS [52].…”
Section: Discussionmentioning
confidence: 98%
“…The apparent contradictory effects of minocycline on mitochondrial respiration (i.e., stimulation vs. inhibition) have been, in part, previously reported for others drugs such as local anaesthetics [50]. Since activation of NMDA receptors responsible for excitotoxicity imposes a high energetic demand on the in situ mitochondria [51] one could hypothesize that minocycline exerts its neuroprotective effect by affecting bioenergetic functions of mitochondria. Indeed, this effect could be responsible for the recent report showing that minocycline has a harmful effect on patients with ALS [52].…”
Section: Discussionmentioning
confidence: 98%
“…A plausible sequence of events could involve lower production of ATP, resulting in increased ion retention (79) and osmotic pressure that in turn cause bursting of ROS followed by photoreceptor death. Previously it was reported that ATP insufficiency is correlated with the failure of the plasma membrane to maintain Ca 2+ pump function with subsequent overaccumulation of Ca 2+ (80,81). Also it is known that photoreceptor cells die rapidly when retinas are incubated in medium deficient in glucose or other metabolites that fuel ATP biosynthesis (82).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies showed lesser or no efficacy of commercial MnTE-2-PyP 5þ (225,255). In another report, the effects observed were explained by dubious mechanistic considerations (344). We published two reports warning the scientific community to consider the purity of SOD mimics seriously, if proper assignments of the effects are to be made (263,265).…”
Section: Reactivity Towardmentioning
confidence: 99%